PROFIL SIKAP BELAJAR POSITIF SISWA SMP KELAS IX DI SMP N 1 CISEWU GARUT - Riyani Saparida; Teti Sobari; Tuti Alawiyah (IKIP Siliwangi, 2020)
The attitude of children towards school has a very large effect on the success or failure of children's education in school. A positive attitude towards school, teachers, and towards friends will be a great encouragement for children to have good relationships. In this research, the approach chosen is descriptive qualitative. The subjects in this study were 5 students. The results showed that the implementation of group guidance services showed many changes, although not all of them. In general, this change is felt very well in the learning process in this class IX SMP.Keywords: Motivation, Education to college